1998
DOI: 10.1016/s0014-5793(98)01588-9
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor dimers in human and rat brain

Abstract: In order to determine whether dimers of dopamine D2 receptors can occur in mammalian brain, rat and human brain striatal membranes were photolabelled with two radioactive photoaffinity compounds selective for dopamine D2 receptors, [ IPS I]azidophenethylspiperone and [IPS I]-4-azido-5-iodonemonapride. It was found that [IPS I]azidophenethylspiperone only labelled the D2 monomer, while [IPS I]-4-azido-5-iodonemonapride labelled both D2 monomers and dimers, despite the fact that very high concentrations (6 nM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 25 publications
5
79
0
Order By: Relevance
“…1B), similar to that observed by some authors in other cell systems [Farooqui et al, 1992;Zawarynski et al, 1998;Lee et al, 2000;Scarselli et al, 2001]. This heterogeneity can be explained by homodimerization [Zawarynski et al, 1998;Guo et al, 2003;Lee et al, 2003] and heterooligomerization of the D2 receptor [Rocheville et al, 2000;Canals et al, 2003: Kearn et al, 2005. Immunoprecipitation detection analysis with a monoclonal antibody only detected a predominant broad band of an apparent molecular mass of 50 kDa that can correspond to both isoforms (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1B), similar to that observed by some authors in other cell systems [Farooqui et al, 1992;Zawarynski et al, 1998;Lee et al, 2000;Scarselli et al, 2001]. This heterogeneity can be explained by homodimerization [Zawarynski et al, 1998;Guo et al, 2003;Lee et al, 2003] and heterooligomerization of the D2 receptor [Rocheville et al, 2000;Canals et al, 2003: Kearn et al, 2005. Immunoprecipitation detection analysis with a monoclonal antibody only detected a predominant broad band of an apparent molecular mass of 50 kDa that can correspond to both isoforms (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Figure 1B shows the Western blot analysis of membrane proteins extracted from rat brain and testis (lanes 1 and 2, respectively). The D2 receptor antibody reacted with two bands that migrated with an apparent Mr of 47-50 kDa and bands with a higher molecular mass which could correspond to oligomerizations described previously for D2 receptor in other cell systems [Zawarynski et al, 1998;Lee et al, 2000]. The peptide pre-adsorbed antiserum control showed no stain for D2R testis membrane proteins (lane 3).…”
Section: Expression Of Dopaminergic D2 Receptor In Rat Testismentioning
confidence: 54%
“…D2 dimer and higher-order oligomers may be partially SDS resistant (Zawarynski et al, 1998); however, Guo et al (2003), using cysteine cross-linking, have shown that the D2 receptor is a native homodimer but does not survive detergent solubilization. Because of the potential for disulfide linkages that could be induced by METH-induced ROS formation and the fact that, like DAT, the D2 receptor is found presynaptically on DA nerve terminals, effects of METH treatment on this protein were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the binding data used in the current analysis, measuring ligand binding to cloned human receptors expressed in cell culture systems, may be distinct from binding to limbic neurotransmitter receptor populations in vivo. Differences in receptor phosphorylation, glycosylation, and/or dimerization to hetero-oligomers (Nimchinsky et al, 1997;Scarselli et al, 2001;Zawarynski et al, 1998;Lee et al, 2000) between in vivo and cell culture systems lacking post-translational machinery could potentially alter receptor-binding affinity. Additionally, atypical antipsychotic medications as a group tend to have more rapid dissociation rates from DA receptors than typical antipsychotics (Kapur and Seeman, 2001), an effect that might further complicate the relationship between receptor affinity and clinically effective drug dose.…”
Section: Limitationsmentioning
confidence: 99%